(untitled) (MAUSAM, 2010)
The continuous and accurate monitoring of wind speed and direction is of utmost importance to weatherman, particularly during the cyclonic storms. Wind monitoring also helps the meteorologists in tracking the cyclone accurately and estimating their devastating potential. One major disadvantage of all the existing wind monitoring and storing systems is their huge consumption of power, and hence are not suitable during cyclonic storms due to mains power supply failure. So an attempt has been made by the authors to design and develop a low cost, low power, more accurate and maintenance free High Wind Speed Recording (HWSR) System for the coastal meteorological observatories along the East and West Coasts of India. One such system after successful field trials have been installed at Meteorological Office, Puri in the Orissa coast, and 19 more stations are proposed along East and West Coasts of India. The system meets the operational accuracy requirements and vector averaging of wind data as recommended by the World Meteorological Organisation (WMO, 1992). The system design aspects and scope for expansion have been presented in this paper.